Simulation as a tool for analyzing climatic risk to forage sorghum (Sorghum bicolor) production in semi arid region in India: Effects of cultivar and planting date - RAI, SUCHIT K; GUPTA, B R D; KUMAR, SUNIL (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 1997-2000 at Jhansi to quantify the effects of planting dates and cultivars phenology on total dry matter of forage sorghum (Sorghum bicolor (L.)Moench] using CERES-sorghum model for semi-arid regions. The approach was applied to 7 locations (Jhansi, Hisar, Delhi, Ludhiana, Pantnagar, Akola and Rahuri ). Production risk varied with dates of sowing, cuItivar maturity and locations. Highest total dry matter was predicted at early (15 June-5 July) dates of sowing in all locations for late maturing cultivar 4HC 136' which ranged between 7.7 and 11.4 tonnes/ha. A1though medium maturing cultivar 'MP Chari' showed lower yield than late cultivar but it was found suitable and stable under late sowings (25 July and 5 August) in all the locations. Sowing date beyond 25 July predicted sharp decline in total dry matter for both medium and late maturing cultivar at Jhansi, Hisar, Delhi and Ludhiana. However, sowing before 15 July selecting a late maturing cultivar gave substantial higher production in all years at Akola, Rahuri, Pantnagar and Jhansi compared with other regions. The probabilistic estimates of total dry matter provided in this study may assist the decision makers of risky choices associated with planting date and cultivar phenology in semi arid regions.